2021
DOI: 10.1021/acs.jced.1c00516
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study on Molecular Interactions of l-Ascorbic Acid/Nicotinic Acid in Aqueous [BMIm]Br at Varying Temperatures and Compositions: Spectroscopic and Thermodynamic Insights

Abstract: Herein, thermophysical properties of l-ascorbic acid and nicotinic acid in different compositions (0.05, 0.10, and 0.15) mol kg–1 of aqueous [BMIm]Br solvent media have been investigated. Different thermodynamic and viscometric parameters have been deduced at distinct temperatures (293.15–318.15 K) and at 0.1 MPa via density, speed of sound, and viscosity data to arrive at logical conclusions. The evaluated parameters include partial molar volume (V ϕ 0), partial molar expansivity (E ϕ 0), partial molar is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…For all the solvent systems as well as assorted vitamin mixtures, the data of dynamic viscosity has been listed in Table . The accomplished values of viscosity of nicotinic acid in water are found to be in conformity with the obtained literature ,,,, at varied temperatures and this has been illustrated by the comparison graph as shown in Figure S5 (ESI). Further, the viscosity data of [C 4 mim]­[Cl] in water have also been compared with the literature at different temperatures (Figure S6).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…For all the solvent systems as well as assorted vitamin mixtures, the data of dynamic viscosity has been listed in Table . The accomplished values of viscosity of nicotinic acid in water are found to be in conformity with the obtained literature ,,,, at varied temperatures and this has been illustrated by the comparison graph as shown in Figure S5 (ESI). Further, the viscosity data of [C 4 mim]­[Cl] in water have also been compared with the literature at different temperatures (Figure S6).…”
Section: Resultssupporting
confidence: 88%
“…Moreover, to authenticate the appropriateness of the estimated velocity of sound data, the experimental and earlier data for nicotinic acid ,,, and [C 4 mim]­[Cl] in water have been analyzed graphically and shown in Figures S3 and S4 (ESI), respectively, which are in agreement with each other. Furthermore, we have attained that the K ϕ,s values are negative for both the considered vitamins in water and in (0.05–0.15) mol kg –1 aqueous IL systems; furthermore, these negative values are escalating with the increase in concentrations of both vitamins.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Δ tr V 0 ϕ has been deliberated by means of the below-ascribed relation Also, the V 0 ϕ of domiphen bromide/semicarbazide hydrochloride can be expressed as a summation of various volumes as presented below where V shrinkage is contraction/depreciation in volume occurring as a result of extensive solvent–solvent interactions, V void is volume allied to empty spaces, and V vw is the van der Waals volume of the taken drugs in the solution. Furthermore, the contribution of V vw and V void is equivalent in water and in maline + water solutions . The deliberated data of Δ tr V 0 ϕ are displayed in Table .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Kwaśniewska and Kiewlicz [6] studied the interactions between cetyltrimethylammonium bromide and AA, and found the existence of ion-ion, ion-dipole and hydrogen bonding interactions based on tensiometric and spectroscopic analysis. Richu and Kumar [7] investigated the thermophysical properties of AA in aqueous [C 4 mim]Br (1methyl-3-butylimidazolium bromide) with varying temperatures and compositions, thereby concluding the supremacy of ion-dipole and dipoledipole interactions in the system. Tian et al [8] found that chitosan and AA could form a soluble complex through ionic interaction.…”
Section: Introductionmentioning
confidence: 99%